Morphological Errors in Everyday Life: A Portrait of Critical Literacy of Elementary School Teacher Candidates to Support Quality Education - Nanda Veruna Enun Kharisma; Dhesta Youlandi Rahayu Sulistiyawati (Universitas Negeri Surabaya, 2026)
This study aims to analyze morphological errors in everyday Indonesian language use and to examine how prospective elementary school teachers employ these errors as a medium for practicing critical literacy skills in alignment with SDG 4 on quality education. Employing a descriptive qualitative design, data were collected from 30 students through 200 everyday texts (e.g., banners, social media posts, and student notes), analytical tasks, and 10 semi-structured interviews. A total of 87 instances of morphological errors were identified and classified into affixation (52%), reduplication (29%), and composition (19%). Critical literacy skills were assessed using a rubric consisting of five indicators: identification, analysis, evaluation, reflection, and transformation. Findings revealed that most students achieved high performance in identification (90%) and analysis (75%), while lower performance was observed in reflection (60%) and transformation (55%). These results indicate that although students are capable of detecting and analyzing morphological errors, they require further pedagogical support to strengthen reflective and transformative practices. The study highlights the pedagogical potential of integrating morphological error analysis into language education as a concrete strategy for developing critical literacy and supporting the objectives of SDG 4.